Estudio comparativo entre los niveles de perfil tiroideo y glucosa basal en pacientes diabéticos y no diabéticos de 40 -80 años que acuden al hospital básico de Yanzatza. - Torres Cabrera, Ana Elizabeth (2013)
In patients with type 2 diabetes the risk of thyroid abnormalities is two to three times higher than in the non-diabetic population, because both diseases occur more frequently as people age, (1) why did the interest to conduct this study, which is designed to determine: thyroid profile levels and fasting glucose in diabetic and no diabetic persons who attended the Yanzatza Base Hospital, at what age are the most common thyroid disorders and thyroid dysfunction influence in relation to high levels of glucose, which was conducted by a comparative descriptive study, whose sample consisted of 82 persons 40-80 years later analysis preceded the Basal glucose, TSH, T3 and T4 using techniques Roche and Accu-bind respectively. After analysis of the results it was concluded that the controlled diabetic patients showed that most normal glucose with respect to their normal values prevailed thyroid profile, obtained in the non-diabetic glucose level and thyroid profile within the ranges normal. However both groups had low thyroid disorders, especially in people over 60 years. It also concluded that TSH levels did not maintain direct relationship with increasing glucose. Keywords: Hypothyroidism, Hyperthyroidism, Diabetes mellitus, basal glucose, TSH, T3, T4.